Disabling Intervention: Intellectual Disability and the Justification of Paternalism in Education - McDonough, Kevin; Taylor, Ashley (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
This paper criticizes mainstream philosophical justifications for paternalism in children’s education, highlighting their exclusion of students labelled with intellectual disability. Most philosophical justifications of paternalism presume “able-mindedness” – that is, they presume that learners possess the potential to develop capacities of rationality and autonomy considered normal – and normatively superior – for adults. Prioritizing these able-minded norms obscures educationally worthwhile communicative, reasoning, and behavioural capacities that diverge from able-minded norms, but which nevertheless express forms of rational and epistemic agency that are educationally beneficial. The paper argues that able-mindedness therefore constitutes a conceptually impoverished basis for educational paternalism. A number of harmful educational implications of able-minded educational paternalism are explored and a more promising and inclusive avenue for justifying educational paternalism is briefly outlined.